الخطاب الديني في الجزائر ومحاربة التطرف - شويني, علي; بدة, فوزية (جامعة الوادي - University of Eloued, 2023)
الملخص لقد شهد الخطاب الديني بالجزائر مخاطر عسيرة نتيجة ما تشهده الساحة العالمية والوطنية، في ظل تزايد ظاهرة التطرف والغلو، وكذلك نتيجة وجود حراك الاجتماعي للشارع كون أن هذا الأخير فرصة مواتية لبث أفكارهم الايديولوجية بهدف إيجاد حالة من الفوضى وإحلال الفتن والفرقة بين أبناء الوطن الواحد، وهذا راجع الى عدم وجود الفاعلية على مستوى الخطاب الديني والمسجدي عموما، باعتباره أنه أصبح شبه جامد ولا يتحرك إلا قليلا. تفرض الضرورة اليوم إعادة بعث الخطاب الديني في الجزائر من أجل محاربة الإرهاب والتطرف العنيف، ونبذ كل الإيديولوجيات التي تخالف التوجه العام للدولة، والمذهب القائم، فالخطاب الديني ينبغي عليه أن يكون خطابا معالجا للمقتضيات الواقع والانتماء ورصد الحلول والمشاكل التي يعاني منها المجتمع فالخطاب الديني بالجزائر أصبح يتعرض لمحاولات اختراق عديدة من بعض الجهات التي تحاول إفساد المجتمع الجزائري وبالضبط مذهبه المالكي في ظل كثرة التيارات الجارفة. Abstract: The religious discourse in Algeria has witnessed serious dangers as a result of what is happening at global and national levels, in light of the increasing extremism phenomenon, as well as the presence of the social mobility of the street, since the latter has a favorable opportunity to spread their ideological ideas in order to createchaos and to produce strife and division among the people of one nation. This is due to the lack of effectiveness at the level of religious and mosque discourse in general, as it has become almost stiff and stagnant. The necessity today requires the re-establishment of religious discourse in Algeria in order to fight terrorism and violent extremism, and to reject all the ideologies that contradict the general orientation of the state and the existing doctrine. The required religious discourse is the one that addresses the requirements of reality and belonging, and monitors solutions and problems the community encounter. The religious discourse in Algeria has become subject to many penetration attempts by some parties trying to corrupt the Algerian society and exactly its Maliki doctrine, in light of the many sweeping currents.
مقال
Keywords: الخطاب الديني ، العنف ، الحوار ، الارهاب ، المذهب المالكي; Religious discourse , violence , dialogue , terrorism , Maliki doctrine